The Relationship between Financial Risk and Earnings Management Before and After IPOs: Evidence from Thailand and Singapore - Arunruangsirilert, Teerachai; Sangsuwan, Wattanachai (Thammasat Review, 2026)
This study examines the relationship of financial risk and earnings management in firms undertaking initial public offerings (IPOs) in Thailand and Singapore between 2010 and 2019, a period spanning between the H1N1 and COVID-19 pandemics. Financial risk is categorized into three types: credit risk, liquidity risk, and operational risk. The analysis utilizes structural equation modeling, comprising 622 firm-year observations across four periods: one year before the IPO (T-1), the IPO year (T), one year after the IPO (T+1), and two years after the IPO (T+2). The findings indicate that IPOs have no direct effect on earnings management in any period for either country. However, an indirect effect is observed for Singapore at T-1, where IPOs are associated with increased accrual-based earnings management mediated by credit risk. No indirect effect is found for Thailand across the four periods.